2021
DOI: 10.17691/stm2021.13.5.05
|View full text |Cite
|
Sign up to set email alerts
|

Individual Navigation Templates for Subcortical Screw Placement in Lumbar Spine

Abstract: Subcortical screw placement is currently performed using frontal view fluoroscopy or intraoperative O-arm navigation system. The emergence of a novel technique for spinal navigation based on individual navigation templates created using 3D printing technology determines the need to study their safety and effectiveness in subcortical implantation. The aim of the study was to evaluate and compare the efficacy of subcortical implantation of pedicle screws in the lumbar spine using individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Re-adjust the position of the K-wire will increase the fluoroscopy times; however, to minimize the holding force and stability of the K-wire, repeated attempts should be abandoned. Kovalenko et al [ 24 ] reported that the use of individual navigation templates for pedicle screw placement could significantly reduce the times of intraoperative fluoroscopy. In a study by Hu et al [ 25 ], PVP with 3D-printed navigation templates could reduce fluoroscopy shot times and fluoroscopy dosage during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Re-adjust the position of the K-wire will increase the fluoroscopy times; however, to minimize the holding force and stability of the K-wire, repeated attempts should be abandoned. Kovalenko et al [ 24 ] reported that the use of individual navigation templates for pedicle screw placement could significantly reduce the times of intraoperative fluoroscopy. In a study by Hu et al [ 25 ], PVP with 3D-printed navigation templates could reduce fluoroscopy shot times and fluoroscopy dosage during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this original procedure, single segment spinal canal decompression, discectomy, interbody fusion and cortical screw fixation are all completed through a small midline incision, minimizing the injury related to the approach and providing another choice of fusion internal fixation for the clinical treatment of lumbar diseases. Over time, surgeons have applied CBT screws through a middle incision to fix two or more levels, which, combined with transforaminal lumbar interbody fusion (TLIF) or posterior lumbar interbody fusion (PLIF), has also been defined as MIDLIF[ 11 - 13 ]. Although many researchers have described techniques with names such as CBT-PLIF or CBT-TLIF, they were in fact instances of MIDLIF[ 14 - 18 ].…”
Section: Introductionmentioning
confidence: 99%